Il parnaso confuso: Azione teatrale in einem akt von Christoph Willibald Gluck - Gluck, Christoph Willibald 1714-1787; Rainer, Ingomar (Wien Universität für musik und darstellende kunst Wien, 2011)
Il Parnaso confuso (Parnassus in Turmoil) is an opera by the composer Christoph Willibald Gluck. It takes the form of an azione teatrale in one act. The Italian-language libretto is by Pietro Metastasio. The opera premiered on 24 January 1765 at Schönbrunn Palace in Vienna. All the members of the cast were archduchesses of the Habsburg family and the work was conducted by the future Emperor Leopold II from the harpsichord.